Strategic gains of by-product marketing: a study on selected companies of Bangladesh - Khan, Tahsan Rahman; Forkan, Golam Mohammad (© 2012 International Journal of Research in Commerce and Management, 2016)
This article was published in International Journal of Research in Commerce and Management [© 2012 International Journal of Research in Commerce and Management] and the definite version is available at : file:///C:/Users/HP/Downloads/ijrcm-1-vol-3_issue-7-art-3.pdf The article website is at: http://ijrcm.org.in/article_info.php?article_id=1929